Analysis of a risk assessment approaches and the development of an integrated internal managament system risk assessment model - Tomov, Kristian (Yearbook Telecommunications, 2014)
Currently, the business world is constantly changing and every day becomes more complicated and more complex. In essence, it is fraught with risk. In recent years, increasing regulatory requirements force companies to spend resources to deal with issues of risk. Properly constituted, risk assessment gives organizations a clear picture of the status of risks in business processes, whether internal or external, imminent or far into the future. The process of risk assessment applied consistently throughout the organization enables better management, identification, assessment and treatment of risks to the business. The present work deals with particular issues related to the risk assessment applied in telecommunication structures.